Desain Implementation of a Photovoltaic for Solar Home System - Thamrin T; Erlangga Erlangga; Susanty W (International Conference on Engineering and Technology Development (ICETD), 2017)
Solar energy is a renewable energy source whose availability is unlimited. To get the electrical energy coming from the sun is required solar panels so that the energy from the sun can turn into electrical energy, Solar technology, also known as photovoltaic (pv) formed in a solar module is formed of a semiconductor material. Semiconductor materials are capable of conducting electric current when there is kinetic energy that drives the electron particles in it to the conduction band. In this case sunlight contains electromagneticwaves or photon energy which is capable of producing kinetic energy to release electron bonds in the semiconductor causing an electric current. This paper describe design and implementing of photovoltaic for solar home system.